في هور الحمار- جنوب العراقCyprinus carpio L. التغيرات السنوية في نشاط مبايض سمكت الكارب الاعتيادي - عبد الرضاساهر; يوسف الخفاجيباسم; عبد مكطوفافراح (University of Thi-Qar Journal of Science, 2019)
The present study includes monitoring the development and maturation in females ovaries Cyprinus carpio L.Which were collected from Al-Hammar Marsh south Iraq, from July 2006 to June 2007 , selected environmental factors( such as air and water temperature ,salinity and day light) were measured in the study area . Depending on values of the Gonado Somatic index (G.S.I) through out the reproductive cycle for one year, there are five growth and maturation stages were observed in the ovaries. namely: Resting stage; it was presented in August & September . The averages of GSI values varied from 0.96-2.20. Developing & Maturing stage; it was presented in October, December, January & February. The averages of G.S.I values varied from 3.56-5.45. Prespawning stage; it was presented in March , with an G.S.I values 12.95 . Spawning stage; it was presented in April & May , with an G.S.I values varied from 3.49-5.19. Post spawning stage; it was presented in June & July ,with averages of G.S.I varied from1.92-2.13 The process of oviposition started from April up to May .This indicate that the spawning period of this species dose not suit the same period of annual prevention 15/2-15/4 ,which is issued by Ministry of Agriculture . Eggs were released in batches .